2003
DOI: 10.1074/jbc.m303842200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Domains of Chicken Mitochondrial Transcription Factor A for the Maintenance of Mitochondrial DNA Copy Number in Lymphoma Cell Line DT40

Abstract: Nuclear and mitochondrial (mt) forms of chicken mt transcription factor A (c-TFAM) generated by alternative splicing of a gene (c-tfam) were cloned. c-tfam mapped at 6q1.1-q1.2 has similar exon/intron organization as mouse tfam except that the first exons encoding the nuclear and the mt form-specific sequences were positioned oppositely. When cDNA encoding the nuclear form was transiently expressed in chicken lymphoma DT40 cells after tagging at the C terminus with c-Myc, the product was localized into nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 56 publications
2
53
1
Order By: Relevance
“…These results indicate that mtDNA is in excess of that needed for normal mitochondrial transcription in Schneider cells. Similar results were obtained upon either suppression or overexpression of the mitochondrial transcription factor A (25,30,31). These data contrast with our finding that mitochondrial transcription factor B2 regulates directly both mtDNA copy number and transcription (25), whereas mitochondrial transcription factor B1 affects neither mtDNA nor transcript levels (26).…”
Section: Discussioncontrasting
confidence: 57%
“…These results indicate that mtDNA is in excess of that needed for normal mitochondrial transcription in Schneider cells. Similar results were obtained upon either suppression or overexpression of the mitochondrial transcription factor A (25,30,31). These data contrast with our finding that mitochondrial transcription factor B2 regulates directly both mtDNA copy number and transcription (25), whereas mitochondrial transcription factor B1 affects neither mtDNA nor transcript levels (26).…”
Section: Discussioncontrasting
confidence: 57%
“…Although the mechanisms by which Lon recognizes its target proteins are not well understood, a recent report showed that E. coli Lon recognizes specific aromatic residue-rich sequences that are hidden in the hydrophobic cores of native structures, but are accessible in unfolded structures (42). Interestingly, the HMG boxes in TFAM contain four conserved aromatic residues within a hydrophobic core, and these residues may be masked when TFAM binds DNA (25,27,29). Another possible explanation is that TFAM not bound to mtDNA becomes exposed to oxidative stress, whereas TFAM bound to mtDNA comprises part of the core of the mitochondrial nucleoids, and is thus surrounded by other proteins (43).…”
Section: Discussionmentioning
confidence: 99%
“…TFAM contains two high mobility group (HMG) amino acid sequence boxes; it binds to mtDNA both specifically and nonspecifically (25). TFAM is essential for mtDNA transcription and for mtDNA packaging in mtDNA maintenance (26)(27)(28)(29)(30). Interestingly, mtDNA and TFAM levels are interdependent, such that knockdown of TFAM results in mtDNA depletion, and reduction of mtDNA copy number causes reduction of TFAM levels (26,29,31).…”
mentioning
confidence: 99%
“…Similar to other HMG box proteins, TFAM is able to bind, wrap, bend, and unwind DNA without sequence specificity (10). Furthermore, TFAM is quite abundant and coats mtDNA in Xenopus laevis (11), chicken (12), mouse (13,14), and human cells (15,16). In vivo data from mouse models has demonstrated that disruption of the Tfam gene leads to loss of mtDNA and embryonic lethality (17), whereas increase of TFAM protein levels leads to increase of mtDNA copy number (13).…”
mentioning
confidence: 99%